SPIRITUALITAS LANSIA DI PANTI WERDHA MOJOPAHIT KABUPATEN MOJOKERTO - Zainuri, Imam (JURNAL KEPERAWATAN SEHAT, 2014)
Spiritual is a need to find meaning and purpose of life, the need to love and be loved as well as a sense of attachment, the need to give and receive forgiveness. A person who is spiritually weak will have an impact in their belief system would be easy to give up, easily discouraged, less interpret his life that shows understanding of the spiritual dimension of the spiritual needs of the still limited. The purpose of this research is to gain an overview of spirituality elderly in nursing homes Mojopahit Mojokerto. The study design is descriptive. The entire elderly population that is at panti Werdha Mojopahit Mojokerto many as 47 elderly. So that in a sample of 42 elderly people get taken by purposive sampling technique. The data were taken using a questionnaire. Having collected the data processing is done editing, coding, scoring, tabulating. The results of this study indicate that the picture of the elderly in nursing homes spirituality MojopahitMojokerto found most respondents were spiritually weak or as many as 22 respondents (52,4%). The number of elderly is spiritually weak due to several factors, namely the developmental stage and family considerations. Elderly expected to be excited in living everyday life with socializing with people around, and a lot of communication.Keywords: spirituality, elderly